A review of absorption heat transformers. (5th December 2015) - Rivera, W.; Best, R.; Cardoso, M.J.; Romero, R.J.
Abstract: In this paper, a review of the performance and development of absorption heat transformers is presented. The review covers the current state of theoretical and experimental studies of single and advanced systems, operating with conventional or alternative mixtures. It also includes their applications, such as waste heat recovery from industrial processes, cogeneration systems and seawater desalination and distillation among others. A bibliographic review has been done based on international journals, dating back from 1986 to date. The review does not intend to be exhaustive, but to reflect the most important research that has been published concerning these technologies. Highlights: We review heat transformer systems in papers that were mainly published in specialized journals. We cover single stage, advanced systems, applications and new working pairs. 168 references were classified and cited. Tables were provided mentioning the author, the working pairs and the relevant implications. Conclusions were provided for the state of the art of heat transformers.